2021
DOI: 10.1017/wsc.2021.57
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the effect of ACCase-targeting herbicides on ACCase activity utilizing a malachite green colorimetric functional assay

Abstract: Research was conducted to evaluate acetyl-Coenzyme A carboxylase (ACCase) enzyme activity using a functional malachite green colorimetric assay previously identified as resistant to sethoxydim, and select aryloxyphenoxypropionate (FOPs) herbicides, fenoxaprop, and fluazifop. Two resistant southern crabgrass [Digitaria ciliaris (Retz.) Koeler] biotypes, R1 and R2, containing an Ile-1781-Leu amino acid substitution and previously identified as resistant to sethoxydim, pinoxaden, and fluazifop but not clethodim w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Clethodim was 17 and 4 times more leaching electrolyte to S than R2 and R1, respectively. Previous research also reported the R1 and R2 biotypes had differential resistance to clethodim when foliar was applied (Yu et al, 2017) and comparatively lower ACCase enzyme activity to clethodim than the other inhibitors sethoxydim, pinoxaden, and fluazifop (Basak et al, 2019;Basak et al, 2021). Using the electrical conductivity assay, the viability of seeds from a variety of crops, including Brassica spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clethodim was 17 and 4 times more leaching electrolyte to S than R2 and R1, respectively. Previous research also reported the R1 and R2 biotypes had differential resistance to clethodim when foliar was applied (Yu et al, 2017) and comparatively lower ACCase enzyme activity to clethodim than the other inhibitors sethoxydim, pinoxaden, and fluazifop (Basak et al, 2019;Basak et al, 2021). Using the electrical conductivity assay, the viability of seeds from a variety of crops, including Brassica spp.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were conducted in the Department of Crop, Soil and Environmental Sciences, Auburn, AL, USA. Two resistant biotypes (R1 and R2) of D. ciliaris with confirmed resistance to select ACCase herbicides (Yu et al, 2017;Basak et al, 2019;Basak et al, 2021), and one susceptible biotype (S), a total of 360 plantlets from each biotype was included in this study. Seeds of the test plant D. ciliaris were grown in separate plastic flats containing commercial potting soil and peat moss (2:1 v/v) under greenhouse conditions.…”
Section: Methodsmentioning
confidence: 99%